Versatile Agar-Zwitterion hybrid hydrogels for temperature self-sensing and electro-responsive actuation - Yang, Jueying (2024)
Although recent years have seen considerable interest in stimuli-responsive hydrogels, their strict preparation conditions and narrow applicability limit their use as diverse sensors and soft robots. Herein, a versatile Agar-Zwirrions hybrid hydrogel actuator (Agar/PSBMA) integrated with simultaneous temperature self-sensing and wide-range electrical response is developed. To prepare the Agar/PSBMA hydrogel, a simple and controllable preforming post-enhancing and mechanical pressing method is used by introducing zwitterions materials into a temperature-sensitive Agar matrix. Owing to the design, the compact multiplex complementary structure generated by this method and the materials can facilitate the improvement of flexibility, stretchability, and toughness while providing mechanical dissipation and adhesion properties. Importantly, the visible detected temperature self-sensing ability during 10–40 °C, and quick and wide-range bending responses of both high-voltage and low-voltage electric fields make it unique over other actuators. Furthermore, the electrical response behavior of the hydrogel is found to be impacted by mechanical characteristics and charge polarization based on the finite element Abaqus simulations analysis. The prepared versatile hydrogels show the potential for applications as soft robotics and controlled transportation of adhered substances while simultaneously monitoring their working temperature, which expands the response range of hydrogel actuators and broadens the scope of application.